Differentiation of Amniotic Membrane Mesenchymal Stem Cells to Cardiomyocytes and the Expression of Nkx2.5 and C-TNT genes - Bahrami , Nastaran; Ale Ebrahim, Mahsa; Salimi, Ali; Roholah, Fateme; Barikrow, Nooshin (Journal of Biological Studies, 2022)
Cardiovascular disease (CVDs) continues to account for more deaths globally than any other single disease. Currently, significant advances have been made in the field of cardiac diseases, and stem cell transplantation-based therapies have emerged as a hopeful therapeutic tool for improving cardiac regeneration and function. Mesenchymal stem cells (MSCs) represent a promising source to be used by regenerative medicine. MSCs have potential to self-renew and discriminate into several cell types. In this study, MSCs were isolated from the amniotic membrane, and their surface markers were identified using flow cytometry. The cells were differentiated to osteoblasts, adipocytes and cardiomyocytes using differentiation medium. RealTime-PCR, and immunochemistry assays were used to assess the expression of cardiac marker genes (Nkx2.5 and C-TNT) and protein. The results confirmed the differentiation of MCSs to cardiomyocytes. NKX2.5 and C-TNT expression level strikingly increased in cardiomyocyte cells compared to hAM-dMSCs. The results of the present study suggested that differentiated human amniotic MSC possessed some characteristics of cardiomyocytes.